Two new species of tribe Coelidiini (Hemiptera: Cicadellidae: Coelidiinae) from the Oriental Reigon - Yang, Li; Jin, Mengyuan; Cao, Yanghui; Zhang, Yalin (Zootaxa, 2025)
Two new species, Cladolidia huagaoxiensis Yang & Zhang sp. nov. from China, and Creberulidia gentingensis Yang & Zhang sp. nov. from Malaysia are described and illustrated in this study.